Structural and Functional Consequences of Connexin 36 (Cx36) Interaction with Calmodulin - Siu, Ryan C. F.; Smirnova, Ekaterina; Brown, Cherie A.; Zoidl, Christiane; Spray, David C.; Donaldson, Logan W.; Zoidl, Georg (Frontiers in Molecular Neuroscience, 2016)
Functional plasticity of neuronal gap junctions involves the interaction of the neuronal connexin36 with calcium/calmodulin-dependent kinase II. The important relationship between Cx36 and CaMKII must also be considered in the context of another protein partner, Ca2+ loaded calmodulin, binding an overlapping site in the carboxy-terminus of Cx36. We demonstrate that CaM and CaMKII binding to Cx36 is calcium-dependent, but independent of each other, with Cx36 engaging with CaM before it reaches the gap junction plaque. Furthermore, Ca2+ loaded calmodulin activates Cx36 channels, which is unique for connexins. The NMR solution structure demonstrates that CaM binds Cx36 in its characteristic compact state with major hydrophobic contributions arising from W277 at anchor position 1 and V285 at position 8 of Cx36. Our results establish Cx36 as a hub binding Ca2+ loaded CaM and they identify this interaction as a critical step with implications for functions preceding the initiation of CaMKII mediated plasticity at electrical synapses.